Dissecting the HGT network of carbon metabolic genes in soil-borne microbiota - Li, Liangzhi; Liu, Yongjun; Xiao, Qinzhi; Xiao, Zhipeng; Meng, Delong; Yang, Zhaoyue; Deng, Wenqiao; Yin, Huaqun; Liu, Zhenghua (Frontiers in Microbiology, 2023)
Soil-borne microbiota is significant for essential life-supporting element cycles. In this study, we predicted horizontal gene transfer (HGT) occurrences established the HGT networks of carbon metabolic genes harbored by the soil-borne microbiota (37,480 genomes of soil isolates) to examine the role of HGT component within microbiological diversification. In the overall HGT network of carbon metabolic genes in soil-borne microbiota, a total of 6,770 nodes and 3,812 edges are present. Among the nodes, phyla Proteobacteria, Actinobacteriota, Bacteroidota, and Firmicutes are predominant. Regarding specific classes, Actinobacteria, Gammaproteobacteria, Alphaproteobacteria, Bacteroidia, Actinomycetia, Betaproteobacteria, and Clostridia are dominant. KEGG functional assignment of glycosyltransferases (18.5%), glycolysis/gluconeogenesis (8.8%), carbohydrate related transporters (7.9%), fatty acid biosynthesis (6.5%), benzoate degradation (3.1%) and butanoate metabolism (3.0%) are mostly identified. Glycosyltransferase involved in cell wall biosynthesis, glycosylation, primary and secondary metabolism (with 363 HGT entries), ranks first overwhelmingly in the list of most frequently identified carbon metabolic HGT enzymes, followed by pimeloyl-ACP methyl ester carboxylesterase, alcohol dehydrogenase and 3-oxoacyl-ACP reductase. HGT events mostly occur in the peripheral functions of the carbon metabolic pathway instead of the core section. The inter-microbe HGT genetic traits in soil-borne microbiota genetic sequences that we recognized, as well as their involvement in metabolism and regulation processes of carbon organic, suggest a pervasive and substantial effect of HGT on the evolution of microbes.